1938
DOI: 10.1111/j.1939-0025.1938.tb06395.x
|View full text |Cite
|
Sign up to set email alerts
|

Enuresis—A method for its study and treatment.

Abstract: IESPITE unremitting efforts, dating from antiquity,' to develop a specific D form of therapy, nocturnal enuresis continues to be generally regarded as an unsolved problem. A review of the several hundred titles constituting the earlier literature on this topic reveals a remarkable array of proposed curative measures, ranging from patent superstitions and magical nostrums to a wide assortment of allegedly scientific methods. Innumerable drugs and hormones;2 special diets (including fresh fruit, caviar, and colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
113
0
3

Year Published

1940
1940
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 434 publications
(118 citation statements)
references
References 13 publications
1
113
0
3
Order By: Relevance
“…In summary, the present data showed that the tone was a punisher and that these punishing properties did not derive simply from the information that the tone provided about slouching. Mowrer and Mowrer (1938) also found that noise was an effective punisher but apparently because it awakened the enuretic patient. The present results reveal that a fairly mild tone can serve as a punisher for the waking individual and suggest its use in other behavior applications as an easily programmed stimulus consequence that does not cause the apprehension caused by electric shock (Powell and Azrin, 1968).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, the present data showed that the tone was a punisher and that these punishing properties did not derive simply from the information that the tone provided about slouching. Mowrer and Mowrer (1938) also found that noise was an effective punisher but apparently because it awakened the enuretic patient. The present results reveal that a fairly mild tone can serve as a punisher for the waking individual and suggest its use in other behavior applications as an easily programmed stimulus consequence that does not cause the apprehension caused by electric shock (Powell and Azrin, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…Only one example of this approach seems to have been developed and proven. In treating bedwetting, Mowrer and Mowrer (1938) developed a special bed pad that sounded an annoying tone when urine caused an electrical current to flow through wires imbedded in the pad. The result was that bedwetting decreased.…”
mentioning
confidence: 99%
“…This criterion excluded the behavior therapy literature based on Pavlov's and Hull's systems (see, e.g., Jones, 1924;Mowrer & Mowrer, 1938;Salter, 1961;Wolpe & Lazarus, 1966), even though Pavlov's science was (and is) included in behavior analysis (see, e.g., Keller & Schoenfeld, 1950, pp. 1-35;Skinner, 1953, pp.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…These include Mary Cover Jones's (1924) article, ''A Laboratory Study of Fear: The Case of Peter,'' which reported eliminating a young boy's fear of rabbits through, in part, Pavlovianbased systematic desensitization (Kazdin, 1978, pp. 130-134;see Jones, 1974); Mowrer and Mowrer's (1938) article, ''Enuresis: A Method for Its Study and Treatment,'' which reported reducing children's nocturnal enuresis with their Hullian-based ''bell-and-pad'' method (Kazdin, 1978, pp. 137-140; see Mellon & McGrath, 2000); and Paul Fuller's (1949) article, ''Operant Conditioning of a Vegetative Human Organism,'' which reported increasing the arm movement of a comatose patient through reinforcement (see Boyle & Greer, 1983).…”
mentioning
confidence: 99%
“…A reprimand was given when pants wetting occurred whereas positive reinforcement was given for proper toileting. Results with four profoundly retarded children indicated the reliability of the apparatuses in practice and the effectiveness of a toilet training program that used the two apparatuses.Nocturnal incontinence of normal children has received extensive study as a result of which effective treatments based on conditioning procedures have been developed (Mowrer and Mowrer, 1938), refined, and systematically evaluated (see review by Lovibond, 1964 (FALL 1971) …”
mentioning
confidence: 99%